169 Exome Sequencing Implicates Endothelial Ras Signaling Network in Vein of Galen Aneurysmal Malformation. (April 2023) - Mekbib, Kedous Y.; Zhao, Shujuan; Nelson-Williams, Carol; Prendergast, Andrew; Zeng, Xue; Rolle, Myron; Shohfi, John; Smith, Hannah; Ocken, Jack; Moyer, Quentin; Piwowarczyk, Paulina; Allington, Garrett; et al.
Abstract : INTRODUCTION: Early neurovascular development is a complex and intricate process with devastating consequences when impaired. Vein of Galen Aneurysmal Malformations (VGAMs) are the most common and severe neonatal arteriovenous malformation and often present with high-output heart failure, hydrocephalus, neurodevelopmental delay, and brain hemorrhage. Despite their prevalence and severity, little is known regarding their genetic pathomechanism. METHODS: Genetic samples were collected from 114 VGAM probands, including 90 trios, from multiple sites. Collected specimens underwent whole exome sequencing, pathway analysis, and select ACVRL1 and EPHB4 mutations identified via sequencing were then studied in zebrafish models. RESULTS: Exome sequencing revealed a genome-wide significant burden of de novo mutations in Ras suppressor p120 Ras-GAP (RASA1) (enrichment = 324-fold; p = 4.8 x 10 -7 ). Damaging transmitted variants were enriched in p120 Ras-GAP negative regulator Eph-B4 (EPHB4) (odds ratio = 27.4; p = 1.7 x 10 -6 ). Eph-B4 missense variants caused loss of receptor tyrosine kinase activity constitutive Ras activation. Other probands had pathogenic variants in OMIM vascular disease genes PTNPN11, NOTCH1, and ACVRL1; the latter we found mutated in an ultra-rare multi-generational VGAM family. Pathway analysis identified enrichment of rare, damaging de novo and inherited variants in a network of interacting OMIM vascular disease genes involved in axon guidance (FDR = 2.3 x 10-5; enrichment = 3.65-fold). In zebrafish, the functional studies of ACVRL1 and EPHB4 confirmed severe vascular defects in mutant embryos. CONCLUSIONS: These results demonstrate that genetic regulation of a RASA1-centered Ras signaling hub is critical for cerebrovascular development and is impaired in VGAM pathogenesis. This finding has significant implications for the genetic counseling of patient families and the development of targeted therapeutics for VGAM neurovascular disorders.